Existence Explanation of the Terrorist Sects Through the Concepts of the Neutrosophic Theory ISIS as a Model - Huda Khalid; Ahmed Salama; Ahmed Essa (University of Mosul-college of Basic Education, 2024)
This article has presented a link between many of the recent events that have been exposed to regions in the Arab world, including Iraq, Syria, Libya, Egypt and others, and a new philosophical and mathematical concept called (The Neutrosophic Logic), through which the data of any problem can be analyzed according to a new perspective that is likely to exist concepts of truthiness, Indeterminacy, and Falsity simultaneously in the same problem.